2024
DOI: 10.2174/0929867330666230309143711
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Virtual Screening, Molecular Docking, Molecular Dynamics Simulation, and Metabolic Reactivity Studies of Quinazoline Derivatives for their Anti-EGFR Activity Against Tumor Angiogenesis

Abstract: The development and progression of tumour cells are solely and utterly dependent on the phenomenon of angiogenesis to furnish the necessary supply of oxygen and nutrients and waste removal mechanisms to tumour cells. The phenomenon of tumour angiogenesis itself results from the over-expression of various receptor tyrosine kinases like EGFR, VEGFR, PDGFR, FGFR, etc. EGFR tyrosine kinase is involved in the growth, development, proliferation, and metastasis of various cancers, including ovarian cancer, NSCLC, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For patients with esophageal squamous cell carcinoma who cannot tolerate chemoradiotherapy, the administration of erlotinib combined with radiotherapy was more tolerable and effective ( Zhai et al, 2013 ). The targeted search for improved inhibition of angiogenesis continues and resulted in the design of more efficient inhibitors of EGFR signaling ( Shah et al, 2023 ), although clinical testing is required before those drugs can be implemented. Conclusively, the previous studies showed that local control rate and overall survival rate of patients who were treated with angiogenesis inhibitor combined with radiotherapy are significantly improved compared with radiotherapy alone.…”
Section: Radiation Therapy Effects In Tumor Vasculaturementioning
confidence: 99%
“…For patients with esophageal squamous cell carcinoma who cannot tolerate chemoradiotherapy, the administration of erlotinib combined with radiotherapy was more tolerable and effective ( Zhai et al, 2013 ). The targeted search for improved inhibition of angiogenesis continues and resulted in the design of more efficient inhibitors of EGFR signaling ( Shah et al, 2023 ), although clinical testing is required before those drugs can be implemented. Conclusively, the previous studies showed that local control rate and overall survival rate of patients who were treated with angiogenesis inhibitor combined with radiotherapy are significantly improved compared with radiotherapy alone.…”
Section: Radiation Therapy Effects In Tumor Vasculaturementioning
confidence: 99%
“…To effectively combat breast cancer, a multitargeted drug design approach is envisaged. This strategy involves the development of a single drug, capable of simultaneously targeting multiple proteins or pathways associated with breast cancer [ 17 , 18 , 19 , 20 ]. Such a drug would inhibit the oestrogen receptor signalling pathway (1M17), disrupt the overexpression of HER2 (3RCD), introduce vulnerabilities in DNA repair mechanisms (5NWH), and modulate the interactions or functions of proteins regulating BRCA1 (4KD7) [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells can adapt and evolve, rendering these drugs ineffective over time. This adaptability is a significant obstacle in lung cancer treatment and highlights the need for more comprehensive therapeutic approaches [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%